2008
DOI: 10.2337/dc07-1152
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes-Related Complications, Glycemic Control, and Falls in Older Adults

Abstract: OBJECTIVE -Older adults with type 2 diabetes are more likely to fall, but little is known about risk factors for falls in this population. We determined whether diabetes-related complications or treatments are associated with risk of falls in older diabetic adults.RESEARCH DESIGN AND METHODS -In the Health, Aging, and Body Composition cohort of well-functioning older adults, participants reported falls in the previous year at annual visits. Odds ratios (ORs) for more frequent falls among 446 diabetic participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
269
3
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(314 citation statements)
references
References 31 publications
13
269
3
18
Order By: Relevance
“…Findings from an earlier study showed a 100–150% increased incidence of disability among older women with diabetes compared to non-diabetic age peers [46]. Indeed, women with diabetes had a 78% increased risk of mobility-related disability and a 65% higher risk of activities of daily living (ADL) disability [47]. In a sample of over 1000 managed-care patients with diabetes with lower formal education and low physical activity, each was associated with disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from an earlier study showed a 100–150% increased incidence of disability among older women with diabetes compared to non-diabetic age peers [46]. Indeed, women with diabetes had a 78% increased risk of mobility-related disability and a 65% higher risk of activities of daily living (ADL) disability [47]. In a sample of over 1000 managed-care patients with diabetes with lower formal education and low physical activity, each was associated with disability.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of over 1000 managed-care patients with diabetes with lower formal education and low physical activity, each was associated with disability. However, the pathway between diabetes and physical disability is multifactorial, and it is not possible to differentiate cause and effect in a cross-sectional study [47]. This study investigated the relation of the overall disability score and not to domain-specific disability as they relate to diabetes and other health and socio-economic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In the BRAZOS study, the only illness related to a greater risk of falls and fractures in men and women was diabetes mellitus, which has also been demonstrated in other studies 3,21,22 . A number of different mechanisms are considered responsible for this finding, such as peripheral neuropathy, compromised renal function, inadequate glucose control, hypoglycemia, diabetes-related muscle weakness, impaired vision and hearing, and a change in the distribution of body composition 23,24 . We did not study aspects related to sensory or motor peripheral neuropathy, as described by others 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…(86) Weight loss has been linked to falls. (87,88) These adverse effects of weight loss on bone and muscle have raised concerns about recommending weight loss in the elderly who may be at increased fracture risk. (85) Some randomized controlled trials of weight loss in the elderly have been proven effective and have demonstrated improvements in quality of life, cardiovascular health indicators, and physical function.…”
Section: Weight Loss Among the Elderlymentioning
confidence: 99%